PERAN GURU MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM DALAM MENGELOLA MEDIA PEMBELAJARAN DI MADRASAH IBTIDAIYAH PLUS DARUL ILMI - Hildawati Hildawati (Program Studi PGMI STAI Al Falah Banjarbaru, 2019)
This study discusses the role of Islamic cultural history subjects in managing learning media in Madrasah Ibtidaiyah. The purpose of this study was to determine the role of Islamic cultural history subjects in managing instructional media in Madrasah Ibtidaiyah Plus Darul Ilmi and to find out aspects that support and inhibit the role of Islamic Cultural History subjects in managing instructional media in Madrasah Ibtidaiyah Plus Darul Ilmi. This research uses descriptive qualitative method with the type of field research. The subjects in the study were three teachers of Islamic Cultural History. Based on the results of the study, it is known that the role of Islamic Cultural History subject teachers in managing learning media in Madrasah Ibtidaiyah Plus Darul Ilmi is already good were some Islamic Cultural History teachers have been able to manage and use learning media. Aspects that support and hinder the role of the teacher of Islamic Cultural History subjects in managing instructional media, namely the appropriateness of the media with learning objectives, media support for the content of subject matter, ease of obtaining media, teacher skills in using media, available time to use media, and appropriateness media with the level of thinking of students. Keywords: Role of Teachers, Islamic History, Management, Learning Media, Madrasah.